Clinical-epidemiological features and improvement of botulism laboratory diagnos-102 tics in Irkutsk region - O. A. Noskova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Irkutsk Region is one of the Russian Regions where botulism cases are registered yearly. Botulism morbidity in Irkutsk Region is analysed for the ten-year period (since 2002); its clinical-epidemiological features are revealed at the present stage. Sporadic cases of botulism, are dominated. (81,9 %). From. 2006 in Irkutsk Region botulism share makes 100 % in food poisoning number. A considerable role in the infection transmission plays consumption of fish, mainly smoked or salty Baikal omul (90,9 %). In 30 % of cases injured people purchased fish at private persons in unascertained trade places, 60 % of patients ate own salting fish. In Irkutsk Region botulism is registered more often from July till November with peaks in July (58,3 %) and. September (20,8 %) that is connected, with activation of unprofitable fabricated fish selling in combination, with adverse conditions of this foodstuff storage. Botulism affects various age groups of population with, prevalence of the age category 30-49 years old. (47,8 %). Socially active able-bodied population. (72,3 %) is most often affected that increases the social importance of the disease. Mainly, moderate severe (56, 5 %) and. severe (34,8 %) disease forms were registered. Primary symptoms include two variants - dyspeptically-paralytic and. ophthalmologic-neurological forms. Analysis of botulism etiological structure showed, that the leading part in the disease occurrence in Irkutsk Region belonged to botulinum. type Е (73, 9 %). Clinical material and. foodstuff testing to botulinum toxin presence was conducted in parallel by the standard reaction of biological toxin neutralisation in white mice and dot-immunoanalysis with application of the test system that we have developed. Possibility of dot-immunoassay application in laboratory diagnostics of botulism is estimated as the express method with high specificity, sensitivity and. simplicity.